2007
DOI: 10.2139/ssrn.1021721
|View full text |Cite
|
Sign up to set email alerts
|

A Multinomial Model of Fertility Choice and Offspring Sex-Ratios in India

Abstract: Fertility decline in developing countries may have unexpected demographic consequences. Although lower fertility improves nutrition, health, and human capital investments for surviving children, little is known about the relationship between fertility outcomes and female-male offspring sex-ratios. Particularly in countries with a cultural preference for sons, like India and China, fertility decline may deteriorate the already imbalanced sex-ratios. We use the fertility histories of over 90,000 Indian women in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that preference for male children is still quite strong (Ram, 2012). Charmabagwala (2010) found a positive correlation between family size and offspring sex ratios, suggesting that many families are using sex-selection technologies. Their research also suggests that the more educated and wealthy families have increased access to these technologies, while the demographic transition theory would suggest that the poor and less-educated have a higher need for male children.…”
Section: Socioeconomic Development and Fertilitymentioning
confidence: 99%
“…Recent studies have shown that preference for male children is still quite strong (Ram, 2012). Charmabagwala (2010) found a positive correlation between family size and offspring sex ratios, suggesting that many families are using sex-selection technologies. Their research also suggests that the more educated and wealthy families have increased access to these technologies, while the demographic transition theory would suggest that the poor and less-educated have a higher need for male children.…”
Section: Socioeconomic Development and Fertilitymentioning
confidence: 99%